Assessment of the effect of phototherapy and PRP on the immediate implants: An original research - Harisha Dewan; Shailesh Jain; Tushar; Manoj Kumar Gupta; Rumneet Kaur Billing; C Krishna Tejaswi (Wolters Kluwer Medknow Publications, 2023)
Immediate implants have been gaining popularity in recent times. There are many adjuvant techniques that are followed before implant placement, which have recently shown hopeful results. For this reason, the current comparative study analyzes the effectiveness of platelet-rich plasma (PRP) and photofunctionalization (PF) at a tertiary care dental hospital. In the current clinical trial, 30 subjects were grouped equally to receive immediate dental implants, with one group in which pretreatment of the extraction site was done with the auto-PRP and PF, while the control group received no pretreatment. For 12 months after the placement of the implant, the subjects were observed for alterations in the parameters. The variables analyzed were survival, esthetics, biological integration, and finally the success of the implants in each group. Values were noted and compared using the appropriate statistical tools, while keeping the level of significance at P < 0.05. For the variables of esthetics and survival, no substantial differences were observed in the PRP and PF groups. There was no difference between these experimental groups and the control group. However, there were significant differences for the biological variable as there was more marginal bone loss in the experimental groups. On the whole, the success was greater for the experimental groups than the control group, though not significant. The pretreatment protocols using PRP and PF have shown to improve some characteristics of the immediate implants in the anterior regions. However, further studies are suggested.